Ongoing Esports Gameplay Intentions Pada Gamer Amatir Generasi Y - Arsy, Akhmad; Arafah, Willy (Innovative: Journal Of Social Science Research, 2024)
This research aims to: (1) Analyze the positive influence of Facilitating Conditions on Ongoing eSport gameplay intentions. (2) Analyze the positive influence of Hedonic Motivation on Ongoing eSport gameplay intentions. (3) Analyzing the positive influence of Effort Expentancy on Ongoing eSport gameplay intentions. (4) Analyzing the positive influence of Social Influence on Ongoing eSport gameplay intentions. (5) Analyzing the positive influence of Price Value on Ongoing eSport gameplay intentions. (6) Analyzing the positive influence of Habit on Ongoing eSport gameplay intentions. This research uses hypothesis testing which consists of 6 variables, namely facilitating conditions, hedonic motivation, effort expenditure, social influence, price-value, and habit. From the research results, it can be concluded that ongoing esports gameplay intentions have several variables that have a significant influence on generation Y amateur gamers. Several variables such as facilitating conditions and habits. Meanwhile, for variables that do not have a significant effect, there are variables such as hedonic motivation, effort expectancy, social influence, and price-value.